Vocational and Technology Education: A Tool to Industrialization in Bayelsa State, Nigeria (Global Journal of Human-Social Science, 2022)
The study examined Vocational and Technology Education, a tool to industrialization in Bayelsa state, Nigeria. The design for the study was comparative survey research design. The population of the study was 98 university graduates of vocational and technology education working in Yenagoa Metropolis, Bayelsa State. The population consists 50 males and 48 females respectively. The instrument for data collection was a questionnaire. The instrument was titled "Vocational and Technology Education Industrialization Questionnaire" (VTEIQ). The instrument have three (3) research questions with twelve (12) statement items. instrument was validated by three experts on face, content and construct respectively. The reliability coefficient was carried out using test-retest method which yielded 0.83. Mean with standard deviation were used to answer the research questions. The hypotheses was tested using Z-test analysis at 0.05 level of significance. From the findings, it was revealed that male and female ratings of university graduates of vocational and technology education with respect to job creation, poverty alleviation and self reliance for industrialization in Bayelsa State, Nigeria have a high extent as a tool for industrialization and it also revealed that there is no significant difference between male and female university graduates of vocational and technology education with respect to job creation, poverty alleviation and self reliance.
Keywords: vocational education; technology education; tool and industrialization